Evaluation of Analgesic, Antidiarrheal and CNS Depressant Activity of Seed Extracts of Trigonella foenum graecum L. (Chittagong University Journal of Biological Sciences, 2024)
The methanolic extract of Trigonella foenum graecum L. showed significant peripheral analgesic activity at a dose of 400 mg/kg and 200 mg/kg body weight with percentage of inhibition of acetic acid induced writhing 68.10%(P